Heteropoly Acid Catalyzed Selective Cyclization of 6-Alkyl-3-propargylmercapto-1,2,4-triazin-5(2H)-one - Fatemeh Hakim; Masoumeh Tabatabaee; Majid M. Hheravi; Mina Roshani; Fatemeh F. Bamoharam (E-Journal of Chemistry)
Cyclization of 6-alkyl-3-propargylmercapto-1,2,4-triazin-5(2H)-one, derivatives (2) in the presence of Keggin heteropoly acids, H3PW1212O40, H3PMo12O40, H4SiW12O40 and lacunary Keggin structure (K7PMo2W9O40) afforded 3 (3a = 6-dimethyl-7H-thiazolo[2,3-b][1,2,4]-triazin-7-one and 3b=6-ethyl-3-methyl-7H-thiazolo[2,3-b][1,2,4]-triazin-7-one) in high yields and short reaction times